Practical API Design - Tulach, Jaroslav (Apress, 2008)
You might think more than enough design books exist in the programming world already. In fact, there are so many that it makes sense to ask why you would read yet another. Is there really a need for yet another design book? In fact, there is a greater need than ever before, and Practical API Design: Confessions of a Java Framework Architect fills that need! Teaches you how to write an API that will stand the test of time Written by the designer of the NetBeans API at Sun Technologies Based on best practices, scalability, and API design patterns.